EXCLUSIVE BREAST FEEDING AS AN EFFORT TO OVERCOME STUNTING IN TODDLERS WITH THE FAMILY EMPOWERMENT STRATEGY APPROACH - Rahayu, Dwi; Fresty Africia; Zauhani Kusnul H; Erwin Yektiningsih; ., Yunarsih (Universitas STRADA Indonesia, 2023)
Background : Stunting is a major problem experienced by toddlers in the world and Indonesia is included in the fifth country with the highest number of toddlers experiencing stunting in the world. Method : The research design used is a non-experimental quantitative research design. This type of research is a correlational descriptive study using a cross sectional approach. Result : The results of the study showed that 76% of toddlers who experienced stunting did not get exclusive breastfeeding. Analysis : Some researchers suspect that the effect of exclusive breastfeeding on stunting does not come from aspects of nutritional intake, but from efforts to prevent infection. Conclution : there is a relationship between exclusive breastfeeding and the incidence of stunting in infants.